">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a: \(3x^2+y^2+10x-2xy+26=0\)

\(\Leftrightarrow\left(x^2-2xy+y^2\right)+\left(2x^2+10x+\dfrac{5}{2}\right)+\dfrac{47}{2}=0\)

\(\Leftrightarrow\left(x-y\right)^2+2\cdot\left(x+\dfrac{5}{2}\right)^2+\dfrac{47}{2}=0\)(vô lý)

b: \(\Leftrightarrow3x^2-12x+12+6y^2-20y+\dfrac{50}{3}+\dfrac{34}{3}=0\)

\(\Leftrightarrow3\left(x-2\right)^2+6\left(y-\dfrac{5}{3}\right)^2+\dfrac{34}{3}=0\)(vô lý)

26 tháng 8 2020

Bài làm:

1) Ta có: \(2x^2+5xy+2y^2\)

\(=\left(2x^2+4xy\right)+\left(xy+2y^2\right)\)

\(=2x\left(x+2y\right)+y\left(x+2y\right)\)

\(=\left(2x+y\right)\left(x+2y\right)\)

2) Ta có: \(2x^2+2xy-4y^2\)

\(=\left(2x^2-2xy\right)+\left(4xy-4y^2\right)\)

\(=2x\left(x-y\right)+4y\left(x-y\right)\)

\(=2\left(x+2y\right)\left(x-y\right)\)

26 tháng 8 2020

\(1)2x^2+5xy+2y^2=2x^2+4xy+xy+2y^2=\left(2x^2+4xy\right)+\left(xy+2y^2\right)=2x\left(x+2y\right)+y\left(x+2y\right)=\left(2x+y\right)\left(x+2y\right)\)\(2)2x^2+2xy-4y^2=2x^2+4xy-2xy-4y^2=\left(2x^2-2xy\right)+\left(4xy-4y^2\right)=2x\left(x-y\right)+4y\left(x-y\right)=\left(2x+4y\right)\left(x-y\right)\)

0
0
0